Emerging concepts on drug resistance in bladder cancer: Implications for future strategies. Issue 1 (October 2015) - Massari, Francesco; Santoni, Matteo; Ciccarese, Chiara; Brunelli, Matteo; Conti, Alessandro; Santini, Daniele; Montironi, Rodolfo; Cascinu, Stefano; Tortora, Giampaolo
Highlights We examine the recent findings on the mechanisms of drug resistance in bladder cancer. We report the methods employed in the assessment of these markers. We highlight the potential strategies to overcome such resistance.